INTERNALIZATION OF ISLAMIC EDUCATIONAL VALUES THROUGH THE LIVING QURAN APPROACH IN ISLAMIC BOARDING SCHOOLS IN THE ERA OF SOCIETY 5.0 - Sutrisna Sutrisna; Mukh Nursikin (International Journal of Social Science, 2023)
The focus of the study of the Internalization of Islamic Education Values ​​in the Living Quran Approach at the Era Society 5.0 Islamic Boarding School regarding various events in Islamic Education related to the existence of the Islamic Boarding School Al-Qur'an, attempts to capture the process of internalizing Islamic Education Values ​​at the Era Society 5.0 Islamic Boarding School and society towards the Al-Qur'an 'an, which is not limited to the meaning of the text, but more emphasis on aspects of its application and grounding in everyday life. The application of the Qur'anic texts later became an institutionalized tradition in the daily life of the community and Islamic boarding schools in Era Society 5.0. This study uses a qualitative-naturalistic method by collecting data from both literature research and field research. Field data collection through (1) observation, (2) in-depth interviews, and (3) documentation. The data that has been collected is then followed by the stages of description, reduction, selection, discussion, analysis and conclusion. The results of the first research are the pesantren strategy (1) study of the Koran Interpreneurship, study of the ideal household al-Quran, study of husnul khotimah preparing for death, study of youth and student consultations. The two implementations are (1) direct community practice with the students' real work program (PKNS), (2) implementation of Ramadan activities and also Islamic holidays at mosques or prayer rooms in the target villages of the pondok (3) Educate the students to play an active role in in preaching in the community (4) Develop life skills that have been taught in Islamic boarding schools. (5) Provide new experiences to students about the challenges of living in the future society. (6) Establishing friendship between Islamic boarding schools and the community, (7) As an information center and source of socio-religious studies (8) Technology and information become a pattern in Islamic boarding schools' activities with the community